Needle tract seeding after endoscopic ultrasound‐guided tissue acquisition of pancreatic tumors: Nationwide survey in Japan. Issue 7 (29th June 2022) - Kitano, Masayuki; Yoshida, Makoto; Ashida, Reiko; Kita, Emiri; Katanuma, Akio; Itoi, Takao; Mikata, Rintaro; Nishikawa, Kenichiro; Matsubayashi, Hiroyuki; Takayama, Yukiko; Kato, Hironari; Takenaka, Mamoru; et al.
Abstract : Objectives: Endoscopic ultrasound‐guided tissue acquisition (EUS‐TA) plays a crucial role in the diagnosis of pancreatic tumors. The present study aimed to investigate the current status of needle tract seeding (NTS) after EUS‐TA of pancreatic tumors based on a nationwide survey in Japan. Methods: Patients who underwent surgical resection of primary pancreatic tumors after EUS‐TA performed between April 2010 and March 2018 were surveyed. The incidence rates of NTS were determined, and compared in patients with pancreatic ductal adenocarcinomas (PDACs) and other tumors, and in patients who underwent transgastric and transduodenal EUS‐TA of PDACs. The detailed features and prognosis of patients with NTS were also assessed. Results: A total of 12, 109 patients underwent surgical resection of primary pancreatic tumors after EUS‐TA. The overall incidence rate of NTS was 0.330%, and the NTS rate was significantly higher in patients with PDAC than in those with other tumors (0.409% vs. 0.071%, P  = 0.004). NTS was observed in 0.857% of patients who underwent transgastric EUS‐TA, but in none of those who underwent transduodenal EUS‐TA. Of the patients with NTS of PDACs, the median time from EUS‐TA to occurrence of NTS and median patient survival were 19.3 and 44.7 months, respectively, with 97.4% of NTS located in the gastric wall and 65.8% of NTS resected. The patient survival was significantly longer in patients who underwent NTS resection than in those without NTS resection ( P  = 0.037). Conclusions: Needle tract seeding appeared only after transgastric not after transduodenal EUS‐TA. Careful follow‐up provides an opportunity to remove localized NTS lesions by gastrectomy.